Upaya orang tua dalam pembentukan karakter kebangsaan anak usia dini melalui cara memilih produk - Priyanto, Anang; Widiarti, Pratiwi Wahyu; Endarwati, Lies (Universitas Negeri Yogyakarta, 2016)
The purpose of this research is to find out parent efforts to build young children character, parent behavior to choose daily needs and to develop model of character building by selection of products on young children. This is a survei and mixed method model. The results of this study were (1) Parent skill in choosing Indonesian product are poor 25.1%, fail or medium 53.9%, and good 21% product selectivity. The most committed effort by parent to make their children love Indonesia product. The second place is by introducing Indonesian product to their children by using and wearing Indonesian product. Parent is easier Indonesian product by seeing the brand. Parent find it is difficult to identify Indonesian product in the global era.